Association between PLA2R1 rs4664308 and susceptibility to idiopathic membranous nephropathy: Protocol for a systematic review and meta-analysis of case-control studies. Issue 45 (6th November 2020) - Qiu, Jing Yi; Wu, Xuan Gao; Zhang, Ting; Park, Sunmin
Abstract : Abstract: Previous studies have evaluated the association between the phospholipase A2 m-type receptor ( PLA2R1) rs4664308 polymorphism and the risk of idiopathic membranous nephropathy (IMN), but the results need to be integrated. We hypothesized that the PLA2R1 rs4664308 polymorphism is associated with IMN risk in different ethnicities and assessed this hypothesis by using meta-analysis and case-control studies. A literature searches on PLA2R1 rs4664308 and IMN risk was conducted using the EMBASE, PubMed, Cochrane Library, and Chinese Medical Databases. The relationship between PLA2R1 rs4664308 and IMN risk was evaluated in 5 genetic models, namely, allelic (AG), recessive (RG), dominant (DG), homozygous (HMG), and heterozygous (HTG) models. Subgroup analysis was conducted by ethnicity on Asian and non-Asian populations. Eight sets of data from 6 articles met study objectives were selected and 6797 subjects (IMN: 2324 Controls: 4, 473) were included. Heterogeneity was found in the DG, HMG, and HTG models but not in the AG or RG models. The minor allele(G) of PLA2R1 rs4664308 showed a significant negative correlation with IMN risk in all genetic random models: odds ratio of AG: 0.44(0.37-0.51), RG: 0.35(0.29-0.42), DG: 0.38(0.31-0.48), HMG: 0.26(0.19-0.37), and HTG: 0.61(0.48-0.77; P  < .00001), and Asians and non-Asians showed the same effect of PLA2R1 rs4664308 on IMN risk. Analysis of Asians and non-Asians revealed no publication bias in any of the 5 genetic models. The minor allele of PLA2R1 rs4664308 has a protective activity against IMN in Asians and non-Asians. It provided new insights into potential curative and preventative treatments for IMN.